Crystal structure and electrical conduction of the organic–inorganic compound (C6H9N2)2ZnI4. (15th May 2019) - Mao, Wenhui; Wang, Jilin; Liao, Hejie; Zhou, Bing; Zheng, Guoyuan; Mo, Shuyi; Long, Fei; Zou, Zhengguang
Graphical abstract: Organic–inorganic single crystal (C6 H9 N2 )2 ZnI4 was successfully prepared using slow evaporation solution method under a relatively moderate condition. The (C6 H9 N2 )2 ZnI4 had a Zero-dimensional consists of two [C6 H9 N2 ] + cation and an asymmetric unit of one anionic tetrahedral [ZnI4 ] 2− . And the sample presented relatively perfect thermal stability up to 260 °C and wide band gap about 3.33 eV which was consistent with the theoretical value. Meanwhile, the compound electrical properties and alternating current (AC) conductivity mechanism were also discussed in detail. Abstract: The organic–inorganic hybrid compound (C6 H9 N2 )2 ZnI4 was prepared by the slow evaporation method at room temperature. The single crystal X-ray diffraction results indicated that the (C6 H9 N2 )2 ZnI4 crystal was a monoclinic system with the space group P 21 / c at room temperature. The compound displayed typical Zero-dimensional (0D) consists of two [C6 H9 N2 ] + cation and one anionic tetrahedral [ZnI4 ] 2− . The sample presented relatively perfect thermal stability up to 260 °C and wide band gap about 3.33 eV which was consistent with the theoretical value. Furthermore, the electrical properties were characterized by impedance spectroscopy with the 209 Hz–5 MHz frequency from 308.15 K to 333.15 K. The alternating current (AC) conductivity of the compound was discussed using Jonscher's law: σ f = σ dc + A f s and the conduction could be attributed to the correlated barrier hopping (CBH) model. Therefore, this kind of organic–inorganic hybrid compound will be a promising candidate for optical and electronic applications.